A Fully Degradable, Bio‐Safe Supercapacitor Targeting for Harmless Disposal of Energy Storage Devices - Chang Xu; Shiqiang Guan; Xijing Zhuang; Xufeng Dong (EcoMat)
ABSTRACT Supercapacitors show broad application prospects as promising energy supply units for future integrated or even implantable electronic devices, but their poor degradability and high biotoxicity severely limit their further development. Regarding this, future‐oriented supercapacitors with fully degradable behavior and excellent biosafety have been prepared through the wide application of degradable polymers and a rational encapsulation and isolation strategy. The combination of self‐supporting pulp fiber/graphene composite electrodes and guar gum gel electrolyte endows the devices with ideal rate performance and long lifetime. The devices demonstrate extremely low cytotoxicity and satisfactory biocompatibility. The implantation caused no significant rejection and did not affect the survival status of the SD rats, suggesting the possibility of powering implantable electronics. Notably, all components of the device (electrodes, electrolyte, substrate, and encapsulation materials) do not contain hazardous or non‐degradable materials, allowing for true complete degradability. The preparation strategy and material selection in the study are expected to be generalized to a wide range of energy storage systems, providing some reference and guidance for the harmless disposal of energy storage devices and even microelectronics.